LEARNING MOTIVATION AS THE BASIC NEEDS IN IMPROVING ENGLISH SKILLS FOR NON- EFL LEARNERS COOPERATIVELY (IKIP Siliwangi, 2021)
The language of English has been used for many years before. The importance of the English language used has been considered by many students in school activities. Unfortunately, some students cannot master English language skills easily. There are some students’ perception about the difficulties of learning English; some of them are students who have the low spirit of English learning process. English learning motivation is one of the fundamental requirements in the process of learning effectively. Motivation in learning English is a part of intrinsic factors from the students. Students have high and deep motivation in learning will gain the objective of learning well. Therefore, both teachers and students must keep improving the learning motivation to the students in the process of learning English both inside and outside of the class. This paper examines current views and scientific proof about the nature of learning motivation in improving non-English foreign language learners. This study is widely used to generate the diverse interests of teachers to the importance of motivation used in the process of English learning, especially for non-native English learners. Keywords: English Language, English Learners, Learning Motivation, Cooperatively